Upaya Perawatan Odgj Dengan Gangguan Proses Pikir Waham Dan Defisit Perawatan Diri Di Kecamatan Kampung Melayu Kota Bengkulu - Lola Emelia; Shasikirana Fitria; Novia Adillah; Putri Wulan Dari; Chesy Okta Wulandari; Resta Nopita Sari; Ade Herman Surya Direja (Jurnal Dehasen Untuk Negeri, 2024)
Delusions are erroneous beliefs that arise from making inappropriate conclusions about external reality, and are then fiercely defended. This is a disorder in which a person experiences a decrease or distortion in their understanding of reality, making it difficult to differentiate between reality and fantasy. Handling delusional thought disorders is often considered a complicated task. Method: The approach used in this Community Service activity is an interview with ODGJ, delusional thought process disorders and self-care deficits illustrate the essence of the implementation of ODGJ treatment carried out by our team in the Kampung Melayu city area. Bengkulu. Objective: to implement SP1 delusions (identification of signs and symptoms of delusions) in people with mental disorders (ODGJ), Benefits: to determine the mental disorders suffered by clients, to provide self-care to clients, to provide food and drink intake. Results: At this meeting, the presence of ODGJ patients was acknowledged when the event started by opening the session, where the team introduced themselves and explained the purpose of organizing the event. The next step includes carrying out direct care for ODGJ patients with full attention to avoid potential resistance from the patient. After that, a question and answer and evaluation session was held.